2021
DOI: 10.1108/ejim-01-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

How can open innovation contribute to circular economy adoption? Insights from a literature review

Abstract: PurposeDespite the potential of open innovation (OI) to reduce barriers to the adoption of the circular economy (CE), little is known about the integration of the two themes and how OI could contribute to a more sustainable economy. The objective of this study is to investigate how OI can contribute to the adoption of the CE.Design/methodology/approachThis study adopts a systematic review of the literature sampled from the Scopus and Web of Science scientific databases.FindingsThe main findings of the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 88 publications
0
19
0
1
Order By: Relevance
“…Conveners strive for balancing of collaboration and competition to address interconnected, systemic issues. Their approaches root in novel forms of collaboration and value co‐creation that deviate from traditional “siloed” cost–benefit analyses (Table 3; Brown et al., 2021; Henry et al., 2021; Jesus & Jugend, 2023). Circular, reciprocal value propositions that are mutually determined by relevant system actors could help to establish a fair value share between disconnected or competing parties (Aminoff et al., 2017; Dagnino, 2007; Ritala & Tidström, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Conveners strive for balancing of collaboration and competition to address interconnected, systemic issues. Their approaches root in novel forms of collaboration and value co‐creation that deviate from traditional “siloed” cost–benefit analyses (Table 3; Brown et al., 2021; Henry et al., 2021; Jesus & Jugend, 2023). Circular, reciprocal value propositions that are mutually determined by relevant system actors could help to establish a fair value share between disconnected or competing parties (Aminoff et al., 2017; Dagnino, 2007; Ritala & Tidström, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As other studies have suggested (Davies and Hodge, 2007;Lehrer and Sneegas, 2018;Leonhardt et al, 2022), the application of Q methodology to identify the points of view of participants may be a key to predicting behavior towards the innovation and sustainability challenges in the agri-food chains. The above perspectives can be encapsulated within the framework of the CE, which manages to combine features of sustainability and innovation (Jesus and Jugend, 2023).…”
Section: Q Methodology: Background and Objectivesmentioning
confidence: 99%
“…We performed a literature review in order to accomplish this research aim. Review papers are important, as they synthesize the current knowledge on a subject and provide avenues for future studies [38]. There are different ways to conduct a literature review; the one provided in this paper can be understood as a framework-based review [39,40].…”
Section: Methodsmentioning
confidence: 99%